2017
DOI: 10.3846/16486897.2017.1339047
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Organic Carbon Content and Leachability of Biomass Waste Biochar for Trace Metal (Cd, Cu and Pb) Speciation Modelling

Abstract: Dissolved organic carbon (DOC) interacts with dissolved trace metal affecting their mobility and bioavailability through the formation of DOC–metal complexes. Several types of biochar (BC) produced from slow pyrolysis of wood chips (WC), lignin (LG), and digested sewage sludge at 450 and 700 °C were tested for DOC leaching via batch and up-flow percolation test methods. Trace metal (Cd, Cu, and Pb) speciation modelling in BC eluates was carried out combining measured data (i.e., DOC, ph, temperature, and disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
2
5
1
Order By: Relevance
“…As for Cr, the concentrations significantly decrease in PSS1 (260°C) and PSS3 (610°C) and increase in PSS2 (420°C). ese results are different from the previous ones [61,91,92], which emphasize the increase of trace metals in the form of oxide and sulfide from 300 to 700°C. For instance, Méndez et al [92] found that biochar derived from sewage sludge pyrolyzed at 500°C retains 31% of Cu, 30% of Pb, and about 28% of Ni, Cd, and Zn compared to the raw feedstock.…”
Section: Effect Of Pyrolysis Temperature On Trace Metal Concentration and Biochar Toxicitycontrasting
confidence: 88%
See 2 more Smart Citations
“…As for Cr, the concentrations significantly decrease in PSS1 (260°C) and PSS3 (610°C) and increase in PSS2 (420°C). ese results are different from the previous ones [61,91,92], which emphasize the increase of trace metals in the form of oxide and sulfide from 300 to 700°C. For instance, Méndez et al [92] found that biochar derived from sewage sludge pyrolyzed at 500°C retains 31% of Cu, 30% of Pb, and about 28% of Ni, Cd, and Zn compared to the raw feedstock.…”
Section: Effect Of Pyrolysis Temperature On Trace Metal Concentration and Biochar Toxicitycontrasting
confidence: 88%
“…As shown in Figure 1, the contents of trace metals in the sewage sludge vary significantly in the following order Zn > Cu > Cr > Pb > Cd, where Zn reaches 3 ppm whereas the content of Cd is only 0.027 ppm. e same trend was reported in the findings of Mancinelli et al [91], as Zn is the element with the highest concentrations followed by Cu, and Cd is the trace metal with the lowest concentrations in the feedstock and the biochars. Previously, Yuan et al [21] explained that Cd tends to volatilize during pyrolysis and the other trace metals initially present in the feedstock generally remain and become concentrated in the biochar.…”
Section: Effect Of Pyrolysis Temperature On Trace Metal Concentration and Biochar Toxicitysupporting
confidence: 86%
See 1 more Smart Citation
“…The high coefficient of variance (>100%) calculated for the means of all the three groups of feedstocks may be due to the wide range of pyrolysis temperatures considered, specifically, BC from cellulose rich feedstock (400-750 °C), BC from lignin-rich feedstock (350-800 °C), and for BC from manure and waste (350-900 °C). Data were retrieved from the following sources: Alburquerque et al 2014;Baltrėnaitė et al 2016;Gaskin et al 2008;Graber et al 2014;Hass et al 2012;Heitkötter, Marschner 2015;Jeong et al 2016;Jones et al 2011;Khan et al 2015;Liu et al 2015;Lu et al 2014;Mancinelli et al 2017;Mukherjee, Zimmerman 2013;Peng et al 2016;Rodríguez-Vila et al 2016;Sáez et al 2016;Smebye et al 2016;Smith et al 2016;Spokas et al 2014;Tang et al 2016;Yue et al 2016;Zeng et al 2015;Zhang et al 2015;Zheng et al 2012 Mean DOC content of BC from manure and waste (Fig. 2c) was the highest (2.24-5.35 g/kg) in the temperature range of 350-450 °C.…”
Section: Resultsmentioning
confidence: 99%
“…A relatively limited fraction of carbon has been reported to be released from BC as DOC (Liu et al 2016), representing between 0.10 and 2.65% of the total carbon (TC) in the BC at 300 °C (Liu et al 2015), between 0.04 and 0.24% of the TC in the BC at 450 °C (Mancinelli et al 2017;Jones et al 2011), between 0.1 and 0.4% of the TC in the BC at 650 °C (Mukherjee, Zimmerman 2013), and between 0.016 and 0.35% of the TC in the BC at 700 °C (Mancinelli et al 2017).…”
Section: Introductionmentioning
confidence: 99%